PEMBERDAYAAN MASYARAKAT DALAM MENUNJANG SEKTOR PARIWISATA BUKIT KASIH (SUATU STUDI DI DESA KANONANG EMPAT KECAMATAN KAWANGKOAN BARAT KABUPATEN MINAHASA) - RONTOS, PRICILIA CHERRY; POSUMAH, JOHNNY HANNY; PLANGITEN, NOVVA (Sam Ratulangi University, 2018)
Abstract: Tourism is the pre-eminent sector of local government in supporting local revenue. However, in itsdevelopment is not followed by the development of the potential of the people around the tourism object. Thisresearch was conducted in Kanonang Village, West Kawangkoan Subdistrict, Minahasa District with the objectof research on empowering the village community in supporting tourism sector of Bukit Kasih. Using thequalitative research designs, it is found that the empowerment of Kanonang Empat community in supportingthe tourism sector of Bukit Kasih has not been seen from the effort to create an atmosphere or climate thatenables the development of community's potential or power, strengthen the potential or power of the communityand protect the community through communities are weak to prevent unbalanced competition.Keywords: Empowerment, Society, Tourism